Center of pressure of a human body using force sensing resistor - Park, C.; Park, S.; Kim, C.H. (Korean Institute of Electrical Engineers, 2014)
An experimental investigation of COP(center of pressure) was performed using FSR(force sensing resistor) and force plate. The FSR sensor system is used as effective device to detect the movement of human body in activities of daily living. It has been shown that the FSR provides the trajectories of COP with repeatability and reliability.
Keywords: Activities of Daily Living; Center of pressure; Experimental investigations; Fall detection; Foot plantar pressures; Force sensing resistor; Human bodies; Sensor systems; Resistors